Dampak Sales Promotion dan Emotions Terhadap Impulse Buying pada Konsumen Shopee: Studi Kasus pada Konsumen Shopee di Surakarta - Shabilla Cahya Masitha; Lukman Hakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the effect of Sales Promotion on Impulse Buying, with Emotions as a mediator among Shopee consumers in Surakarta. A quantitative descriptive method was used, collecting data through an online questionnaire. The sample was selected using a non-probability sampling technique with specific criteria: residing in Surakarta, at least 17 years old, and having previously shopped on Shopee. Data analysis included validity and reliability tests, classical assumption tests, and hypothesis testing using t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that Sales Promotion has a positive and significant impact on both Emotions and Impulse Buying, with Emotions acting as a mediator. Effective promotional strategies by Shopee enhance consumers’ positive emotions, leading to increased impulsive buying behavior and customer satisfaction. However, this study is limited by its narrow scope and the exclusion of other factors that may influence Impulse Buying. Future research should consider additional variables such as psychological conditions, environmental influences, product categories, as well as demographic and personality factors. Expanding the study area is also recommended to improve result validity and provide a broader understanding of consumer behavior in e-commerce.